An Exploratory Study of General Self-Efficacy and Employment in Adults with Retinitis Pigmentosa. (January 2020) - Zapata, Mercedes A.
Introduction: In this study, the author examined the association between general self-efficacy (GSE) and employment status in working-age adults with retinitis pigmentosa (RP; N = 183). The author further examined the associations between employment status and factors that were previously found to be linked to employment outcomes in individuals with visual impairments: educational attainment, mobility tool use (i.e., use of dog guide or cane), ability to drive, age, gender, and age at onset of visual impairment. Methods: Multiple logistic regression was used to analyze cross-sectional data collected online in 2015. Results: Findings indicated that individuals with RP who have a bachelor's degree or higher had significantly higher odds of being employed ( p < .01) and that individuals with RP who use a cane or dog guide had significantly lower odds of being employed ( p < .01). Although not statistically significant, findings further indicated that individuals with RP who have higher GSE had higher odds of being employed ( p = .07) and that individuals who are able to drive had 130% higher odds of being employed ( p = .06). Discussion: Results demonstrated an association between GSE and employment status, after controlling for factors that were previously linked to employment outcomes in individuals with visual impairment. Implications for practitioners: Self-efficacy is an alterable cognitive construct and may be the target of interventions to increase employment outcomes for adults with RP or other eye conditions.